Tislelizumab plus nimotuzumab is effective against recurrent or metastatic oral squamous cell carcinoma among patients with a performance status score ≥ 2: a retrospective study - Wu, Wen-Jie; An, Pu-Gen; Zhong, Yi-Wei; Hu, Xiao; Wang, Lin; Zhang, Jie (Frontiers in Oncology, 2024)
Objectives The efficacy of treatments targeting recurrent or metastatic head and neck squamous cell carcinoma are unsatisfactory in practice for patients with a ECOG PS score ≥ 2. Thus, this study retrospectively evaluated the safety and efficacy of a programmed cell death 1 inhibitor (tislelizumab) combined with an epidermal growth factor receptor inhibitor (nimotuzumab) in treating patients with a PS score ≥ 2 who suffer from recurrent or metastatic oral squamous cell carcinoma (OSCC). Materials and methods Fifteen patients were treated with tislelizumab (200 mg IV Q3W) and nimotuzumab (200 mg IV Q3W). Programmed cell death-ligand 1 (PD-L1) expression in tumor biopsies was assessed with immunohistochemistry. Whole-exome sequencing was used to evaluate treatment efficacy based on PD-L1 expression and gene mutation. Results At a median follow-up of 9.6 months, median overall survival was 10.1 months, and median progression-free survival was 4.0 months. Overall response rate was 40%, with 6/15 patients achieving partial response. Eight patients exhibited nine adverse events, eight out of nine being grade 2 and the remaining being grade 3. Whole-exome sequencing showed that DYNC1I2, THSD7A, and FAT1 mutations were associated with patient prognosis. Conclusion Combination therapy involving tislelizumab plus nimotuzumab is a promising, low-toxicity treatment for recurrent or metastatic OSCC in patients with a PS score ≥ 2.